2004
DOI: 10.1007/s00418-004-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of fibrinolytic components in nasal mucosa

Abstract: Components of the fibrinolytic pathway contribute to diverse pathways in many tissues, in addition to their well-recognized role in degradation of fibrin clots. In this study of nasal mucosa, we investigated the presence of mRNA of tissue-type plasminogen activator (t-PA), urokinase-type plasminogen activator (u-PA), plasminogen activator inhibitor-1 (PAI-1), and plasminogen activator inhibitor-2 (PAI-2) using reverse transcription polymerase chain reaction (RT-PCR) and in situ hybridization, and compared thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…The regulation of t-PA gene expression is not well described. t-PA is produced by a number of airway cells, including mast cells, macrophages, fibroblasts, endothelial cells, glandular cells, and epithelial cells (38,39). Our immunohistochemistry data demonstrated that t-PA staining was most prominently Figure 7.…”
Section: Discussionmentioning
confidence: 80%
“…The regulation of t-PA gene expression is not well described. t-PA is produced by a number of airway cells, including mast cells, macrophages, fibroblasts, endothelial cells, glandular cells, and epithelial cells (38,39). Our immunohistochemistry data demonstrated that t-PA staining was most prominently Figure 7.…”
Section: Discussionmentioning
confidence: 80%
“…The nasal tissues for RNA isolation (20 -30 g) were homogenized, and total RNA was isolated by using the RNeasy Mini kit (Qiagen) as described previously (12,22,23). Total RNA (0.5 g) from each sample was reverse transcribed as described previously (12).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…The nasal tissues for RNA isolation (20 -30 g) were homogenized, and total RNA was isolated by using the RNeasy Mini kit (Qiagen) as described previously (12,22,23). Total RNA (0.5 g) from each sample was reverse transcribed as described previously (12). Real-time quantitative PCR was performed using a TaqMan Gold RT-PCR kit (PerkinElmer Applied Biosystems) and an ABI Prism 7700 Sequence Detection System (PerkinElmer Applied Biosystems) (12,24).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations